Effects of Crushed Ticagrelor Versus Eptifibatide Bolus Plus Clopidogrel in Troponin‐Negative Acute Coronary Syndrome Patients Undergoing Percutaneous Coronary Intervention: A Randomized Clinical Trial. Issue 23 (3rd December 2019) - Marian, Moazez J.; Abu Daya, Hussein; Chatterjee, Arka; Al Solaiman, Firas; Sasse, Mark F.; Fonbah, William S.; Workman, Raymond W.; Johnson, Brittany E.; Carlson, Sarah E.; Brott, Brigitta C.; Prabhu, Sumanth D.; Leesar, Massoud A.
Abstract : Background: After a loading dose of ticagrelor, the rate of high on‐treatment platelet reactivity remains elevated, which increases periprocedural myocardial infarction and injury. This indicates that faster platelet inhibition with crushed ticagrelor (CTIC) or eptifibatide is needed to reduce high on‐treatment platelet reactivity. The efficacy of CTIC versus eptifibatide bolus plus clopidogrel is unknown. Methods and Results: A total of 100 P2Y12 naïve, troponin‐negative patients with acute coronary syndrome were randomized to CTIC (180 mg) versus eptifibatide bolus (180 μg/kg×2 intravenous boluses) plus clopidogrel (600 mg) at the time of percutaneous coronary intervention. High on‐treatment platelet reactivity was markedly higher with CTIC versus eptifibatide bolus plus clopidogrel (42% versus 0%; P <0.001) at 30 minutes and persisted up to 2 hours (12% versus 0%; P =0.01, respectively). Platelet aggregation by adenosine diphosphate dropped faster from baseline with eptifibatide bolus plus clopidogrel versus CTIC (0.5 versus 2 hours, respectively) and was higher with CTIC versus eptifibatide bolus plus clopidogrel at 0.5, 2, and 4 hours after loading dose (53±12% versus 1.3±2%; 35±11% versus 0.34±1.0%; and 23±9% versus 3.5±2%, respectively; P <0.001). Eptifibatide bolus plus clopidogrel, but not CTIC, significantly inhibited platelet aggregation induced by thrombin‐receptor activating peptide. Periprocedural myocardial infarction and injury was higher with CTIC versus eptifibatide bolus plus clopidogrel (48% versus 28%, respectively; P =0.035). Post–percutaneous coronary intervention hemoglobin levels were not different between groups. Conclusions: Eptifibatide bolus plus clopidogrel led to faster and more potent platelet inhibition than CTIC and reduced periprocedural myocardial infarction and injury in troponin‐negative acute coronary syndrome patients undergoing percutaneous coronary intervention, with no significant hemoglobin drop after percutaneous coronary intervention. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT02925923.